Electrochemical element, electrochemical element roll, and method for manufacturing electrochemical element
Patent Information
- Application Number
- CN202580019864.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-14
- Filing Date
- 2025-02-13
- Publication Date
- 2026-10-09
AI Technical Summary
在SOFC、PCFC等中,已知有电解质支承型、电极支承型的燃料电池,但它们特别是在搭载于汽车、无人机等移动设备的情况下,存在不耐冲击、容易破裂的缺点
[0013]根据本发明一方式的电化学元件,能够实现轻量化和耐冲击性的兼顾以及生产率的提高。
Smart Images

Figure CN122893183A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to electrochemical elements, electrochemical element rollers, and methods for manufacturing electrochemical elements. Background Technology
[0002] Solid oxide fuel cells (SOFCs) and proton-conducting ceramic fuel cells (PCFCs) have attracted attention due to their high power generation efficiency and lack of the need for precious metals. Among SOFCs and PCFCs, electrolyte-supported and electrode-supported fuel cells are known, but they suffer from drawbacks, particularly when mounted on mobile devices such as automobiles and drones, including poor shock resistance and susceptibility to breakage. To address these shortcomings, research has been conducted to improve shock resistance, leading to the development of metal-supported fuel cells.
[0003] For example, Patent Document 1 discloses a metal-supported electrochemical element, which has at least a metal substrate as a support, an electrode layer formed on the metal substrate, a buffer layer formed on the electrode layer, and an electrolyte layer formed on the buffer layer.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: International Publication No. 2017 / 047656 Summary of the Invention
[0007] The technical problem that the invention aims to solve
[0008] However, while conventional metal-supported electrochemical elements offer improved impact resistance, their weight due to the metal support structure can make them difficult to handle during installation. Furthermore, when mounted on mobile equipment, they may be a drawback in terms of improving fuel economy. Additionally, the batch production of metal-supported electrochemical elements leads to reduced productivity.
[0009] The purpose of this invention is to provide an electrochemical element that achieves both lightweight and impact resistance as well as increased productivity.
[0010] Technical solutions for solving technical problems
[0011] An electrochemical element according to one aspect of the present invention comprises, in sequence, a glass membrane that allows gas to pass through, an electrode layer, and an electrolyte layer, with a bending radius exceeding 20 mm and less than 200 mm, and the thickness of the glass membrane being more than 20 μm and less than 200 μm.
[0012] Invention Effects
[0013] According to one aspect of the electrochemical element of the present invention, it is possible to achieve a balance between lightweight and impact resistance, as well as increased productivity. Attached Figure Description
[0014] Figure 1 This is a schematic diagram showing the configuration of the electrochemical element in this embodiment.
[0015] Figure 2 This is a flowchart illustrating the manufacturing method of the electrochemical element according to this embodiment.
[0016] Figure 3 This is a diagram illustrating the manufacturing method of the electrochemical element according to this embodiment. Detailed Implementation
[0017] The embodiments of the present invention will now be described in detail. Furthermore, for ease of understanding, the same reference numerals are used to denote the same constituent elements in the accompanying drawings, and repeated descriptions are omitted. Additionally, the scale of the components in the drawings may sometimes differ from the actual scale.
[0018] Figure 1 This is a schematic diagram showing the configuration of the electrochemical element in this embodiment. (e.g.) Figure 1 As shown, the electrochemical element 1 of this embodiment sequentially comprises a glass membrane 2 that allows gas to pass through, an electrode layer 3, an electrolyte layer 4, and a counter electrode layer 5. Furthermore, the bending radius of the electrochemical element 1 is greater than 20 mm and less than 200 mm, and the thickness of the glass membrane 2 is greater than 20 μm and less than 200 μm. With this configuration, the electrochemical element 1 achieves both lightweight design and improved impact resistance. Additionally, because the glass membrane 2 has sufficient flexibility, the electrochemical element 1 can be manufactured using a roll-to-roll method, improving productivity. In other words, the electrochemical element 1 achieves a balance between lightweight design and impact resistance, as well as improved productivity. Furthermore, the bending radius of the electrochemical element 1 can be measured by the following method.
[0019] Prepare multiple vinyl chloride rods with radii ranging from 20 mm to 100 mm, each differing by 10 mm. At 23°C, with the electrochemical element 1 along the rod and the glass membrane 2 side as the outer side, use transparent tape (NICHIBAN "CT405AP-24", adhesive strength 3.93 N / 10 cm) to check whether both sides can be fixed, whether they cannot be fixed, or whether the glass membrane is broken. The minimum radius of the rod that allows for fixing both sides without breaking the glass membrane is defined as the bending radius. The dimensions of the electrochemical element 1 used in the measurement are: a short side of 20 mm and a long side with the same radius as the outer diameter of the rod.
[0020] The bending radius of the electrochemical element 1 is preferably 30 mm or more and 180 mm or less, more preferably 50 mm or more and 150 mm or less. If the bending radius of the electrochemical element 1 is within the above-mentioned preferred range, the electrochemical element 1 can further improve its impact resistance.
[0021] The glass film 2 can have a sheet-like shape. The glass film 2 is formed using a strip of glass. The glass film 2 is obtained by cutting the strip of glass, etc. In addition, in this specification, "strip-like" refers to an elongated shape whose length is sufficiently long relative to its width, such as an elongated rectangle whose length is 10 times or more, preferably 20 times or more, than its width.
[0022] The glass film 2 can be formed using any glass material. The glass material constituting the glass film 2 is preferably inorganic glass. Examples of inorganic glasses, based on composition, include soda-lime glass, borosilicate glass, aluminosilicate glass, and quartz glass; examples based on alkali content include alkali-free glass and low-alkali glass. The content of alkali metal components (e.g., Na₂O, K₂, Li₂O) in the aforementioned glass is preferably 15% by mass or less, more preferably 10% by mass or less.
[0023] The thickness of the glass film 2 is preferably 25 mm or more and 190 mm or less, more preferably 30 mm or more and 180 mm or less. If the thickness of the glass film 2 is within the above-mentioned preferred range, the electrochemical element 1 can be further reduced in weight and its impact resistance can be further improved. In addition, since the glass film 2 is easy to bend, the electrochemical element 1 can be easily manufactured using a roll-to-roll method, which can further improve productivity.
[0024] The glass membrane 2 may have multiple through holes 21. Specifically, the through holes 21 penetrate the upper surface (the surface opposite to the electrode layer 3) and the lower surface (the surface opposite to the electrode layer 3) of the glass membrane 2. This allows gas to permeate from the lower surface to the upper surface of the glass membrane 2, thus providing a PCFC that achieves improved lightweight and impact resistance.
[0025] The through hole 21 can be circular in top view, and its diameter can be between 5 mm and 20 mm. The through hole 21 can be formed, for example, by laser processing.
[0026] The length and width of the glass membrane 2 are not particularly limited and can be appropriately designed according to the size of the electrochemical element 1. The length of the glass membrane 2 is preferably 50 mm or more and 5000 mm or less, more preferably 100 mm or more and 1500 mm or less. The width of the glass membrane 2 is preferably 50 mm or more and 5000 mm or less, more preferably 100 mm or more and 1500 mm or less. The length and width of the glass membrane 2 can be the same or different.
[0027] The density of glass film 2 is not particularly limited; for example, it can be set to 2.3 g / cm³. 3 Above and 3.0 g / cm 3 the following.
[0028] There are no particular limitations on the manufacturing method of the glass film 2; general manufacturing methods can be used. For example, the glass film 2 is manufactured by melting a mixture containing main raw materials such as silicon dioxide and alumina, defoamers such as sodium sulfate and antimony oxide, and reducing agents such as carbon, at a temperature above 1400°C and below 1600°C, forming it into a thin sheet, and then cooling it. To achieve thinner sheets or improve smoothness, the glass film 2 can be chemically ground using solvents such as hydrofluoric acid, as needed.
[0029] The glass film 2 can be formed using conventional methods. For example, slit-drawing, melting, and float glass methods can be used. Among these, the melting method avoids surface contamination by tin or other materials, unlike the float glass method, thus eliminating the need for grinding and easily ensuring surface smoothness and thinness. Therefore, from these perspectives, the melting method is preferred.
[0030] Glass film 2 can be used directly from commercially available glass films, or commercially available glass sheets can be ground to the desired thickness. Examples of commercially available glass sheets include Corning's "7059", "1737" or "EAGLE2000", Asahi Glass's "AN100", NH TechnoGlass's "NA-35", Nippon Electric Glass's "OA-10G", and Shot's "D263" or "AF45".
[0031] Electrode layer 3 is the anode. When electrochemical element 1 is a PCFC, electrode layer 3 is hydrogen permeable. That is, electrode layer 3 has proton (H) permeability. + It has ionic conductivity and does not possess oxygen ion (O) conductivity. 2- Conductivity. The thickness of electrode layer 3 can be set to, for example, more than 1 μm and less than 1000 μm.
[0032] As a material constituting electrode layer 3, and serving as a hydrogen-permeable membrane, examples include Pd (palladium) films and Pd alloy films. Specifically, palladium alloys include Pd-Au (palladium-gold), Pd-Ag (palladium-silver), Pd-Pt (palladium-platinum), and Pd-Cu (palladium-copper). Furthermore, as additive elements, trace amounts of Group 3, Group 4, Group 5, iron group, and platinum group elements can be added to the aforementioned palladium or palladium alloys. Specific examples of additive elements include Y (yttrium), Ho (holmium), Ti (titanium), Zr (zirconium), Ni (nickel), Nb (niobium), V (vanadium), and Ru (ruthenium).
[0033] Electrolyte layer 4 may contain oxides. This allows for the provision of PCFCs or SOFCs that achieve lightweight design and improved impact resistance. When electrochemical element 1 is a PCFC, BaZr can be used as a material constituting electrolyte layer 4. x Ce 1-x-z Y z O3 (BZCY), yttrium-doped barium zirconate (BZY), yttrium-doped barium cerium (BCY), etc. The thickness of the electrolyte layer 4 is preferably 0.1 μm or more and 10 μm or less, more preferably 0.1 μm or more and 1 μm or less.
[0034] Counter electrode layer 5 is the cathode. Counter electrode layer 5 has the function of adsorbing oxygen molecules and dissociating them to ionize them. In counter electrode layer 5, protons conducted via electrolyte layer 4 react with oxygen ions. The thickness of counter electrode layer 5 can be, for example, between 1 μm and 1000 μm.
[0035] As the material constituting the counter electrode layer 5, known materials used as cathodes in fuel cells can be used. Examples of materials constituting the counter electrode layer 5 include La. 0.6 Sr 0.4 Co 0.2 Fe 0.8 Lanthanum strontium cobalt ferrite (LSCF) and Sm 0.5 Sr 0.5 Samarium strontium cobaltate (SSC) such as CoO3, Ba 0.5 Sr 0.5 Co 0.6 Fe 0.4 Barium strontium cobalt ferrite (BSCF) and other minerals such as O3.
[0036] The glass membrane 2, electrode layer 3, electrolyte layer 4, and counter electrode layer 5 can be in contact with each other, or other layers can be disposed between each layer. The electrochemical element 1 can be a glass-supported SOFC or a glass-supported PCFC.
[0037] Figure 2 This is a flowchart illustrating a method for manufacturing the electrochemical element according to this embodiment. Figure 3This is a diagram illustrating the manufacturing method of the electrochemical element according to this embodiment. (As shown...) Figure 2 As shown, the manufacturing method of the electrochemical element 1 in this embodiment includes: step S1, forming an electrode layer 3 on the glass membrane 2 while conveying it in a roll-to-roll manner, the glass membrane 2 having a thickness of 20 μm or more and 200 μm or less and allowing gas to pass through; step S2, forming an electrolyte layer 4 on the electrode layer 3; and step S3, forming a counter electrode layer 5 on the electrolyte layer 4. Therefore, according to the manufacturing method of the electrochemical element 1 in this embodiment, an electrochemical element 1 that achieves improved lightweight and impact resistance can be provided. Furthermore, since the manufacturing is performed using a roll-to-roll manner, the productivity of the electrochemical element 1 can be improved.
[0038] Specifically, such as Figure 3 As shown, using the roller-to-roll transport device 100, a glass film 2 wound into a roller shape is transported from the extraction roller 110 while an electrode layer 3 is formed on the glass film 2 by the processing device 120. Then, by the processing device 120, an electrolyte layer 4 can be formed on the electrode layer 3, and a counter electrode layer 5 can be formed on the electrolyte layer 4.
[0039] The processing apparatus 120 includes, for example, a sputtering device and a screen printing machine. The laminate 9, consisting of a glass film 2, an electrode layer 3, an electrolyte layer 4, and a counter electrode layer 5, transported from the processing apparatus 120, is wound into a roller shape by a take-up roller 130, thereby obtaining the electrochemical element roller 10. The glass film 2, electrode layer 3, electrolyte layer 4, and counter electrode layer 5 are the same as those components of the electrochemical element 1 described above, and therefore their description is omitted here.
[0040] In the manufacturing method of electrochemical element 1, after step S3 of forming counter electrode layer 5, the obtained electrochemical element roller 10 is cut to a predetermined size, thereby obtaining electrochemical element 1. The cutting method of electrochemical element roller 10 is, for example, a method of irradiating the electrochemical element roller 10 with a laser to break the electrochemical element roller 10.
[0041] In the method of using laser irradiation to break the electrochemical element roller 10, any laser irradiation device can be used to break the electrochemical element roller 10. The worktable is movably configured relative to the laser irradiation device, while the laser source is fixedly configured. The laser irradiation device moves the position of the laser irradiating the electrochemical element roller 10 by moving the worktable.
[0042] Examples of lasers include gas lasers such as CO2 lasers and excimer lasers; solid-state lasers such as YAG lasers; semiconductor lasers; and ultrashort pulse lasers.
[0043] like Figure 3As shown, the electrochemical element roller 10 of this embodiment is an electrochemical element 1 wound into a roller shape. That is, the electrochemical element roller 10 has a strip shape and sequentially includes a glass membrane 2 that allows gas to pass through, an electrode layer 3, and an electrolyte layer 4. In addition, the bending radius of the electrochemical element 1 is greater than 20 mm and less than 200 mm, and the thickness of the glass membrane 2 is more than 20 μm and less than 200 μm. With this configuration, the electrochemical element roller 10 can achieve lightweight and improved impact resistance. In addition, the bending radius of the electrochemical element roller 10 can be measured by the bending radius measurement method of the electrochemical element 1 described above.
[0044] Example
[0045] The following examples and comparative examples are used to illustrate the implementation in more detail, but the implementation is not limited to these examples and comparative examples.
[0046] <Fabrication of Electrochemical Components>
[0047] For a 100mm square glass film (manufactured by Nippon Electric Glass Co., Ltd., “OA-10G”) with the thickness shown in Table 1, multiple through holes of 10μm or more and approximately 15μm or less are formed in an area 2.5mm from the center by laser processing to fabricate a glass substrate.
[0048] As the electrode layer, a 200 nm thick Pd film was formed on a glass substrate using DC sputtering. BaCe was used. 0.8 Y 0.2 O3 (BCYO) target and Zr 0.9 Y 0.1 A BaZr film with a thickness of 1 μm was deposited on a Pd film using an O2 (ZYO) target and a high-frequency sputtering method. 0.1 Ce 0.7 Y 0.2 O3 (BZCY) electrolyte membrane. Regarding the high-frequency sputtering conditions, O2 was introduced at a flow rate of 0.1 sccm under vacuum, and Ar was introduced at a flow rate of 49.9 sccm. The substrate temperature was set to 400°C, the sputtering pressure to 2 Pa, and the sputtering time to 7 hours. Furthermore, for the BCYO target, the distance to the glass substrate was 70 mm, and the sputtering output was 70 W; for the ZYO target, the distance to the glass substrate was 120 mm, and the sputtering output was 30 W. La was screen-printed on the front side of the electrolyte membrane as the counter electrode layer. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 (LSCF) powder slurry (manufactured by Fuel Cell Materials).
[0049] Through the above, electrochemical devices of Examples 1-2 and Comparative Examples 1-2, in which a glass membrane, an electrode layer composed of Pd, an electrolyte layer composed of BZCY, and a counter electrode layer composed of LSCF are sequentially stacked, were obtained.
[0050] <Evaluation>
[0051] The bending radius and impact resistance of the electrochemical elements in each embodiment and comparative example were evaluated as follows. The evaluation results are shown in Table 1.
[0052] (Bending radius)
[0053] Prepare multiple vinyl chloride rods with radii ranging from 20 mm to 100 mm, each differing by 10 mm. At 23°C, with the electrochemical element facing outwards from the glass membrane side, use transparent tape (NICHIBAN "CT405AP-24", adhesive strength 3.93 N / 10 cm) along the rod to check whether both sides can be secured, whether they cannot be secured, or whether the glass membrane is broken. The smallest radius of the rod that can be secured without breaking the glass membrane is taken as the bending radius. The electrochemical element used in the measurement has a short side of 20 mm and a long side with the same radius as the outer diameter of the rod. Bending radii exceeding 20 mm but less than 200 mm are evaluated as practically usable, while bending radii less than 20 mm and exceeding 200 mm are evaluated as impractical.
[0054] (Impact resistance)
[0055] The electrochemical element was cut into 5cm × 5cm pieces and attached to a glass plate as an evaluation sample. A puncture rod (0.5mm in diameter) was dropped onto the sample from a height of 10cm at a speed of 20mm / min. The presence or absence of cracks in the glass membrane was visually observed, and the evaluation was carried out according to the following criteria.
[0056] Good: No cracks
[0057] Defect: Cracks present
[0058] If the bending radius is practically usable and has good impact resistance, it is set as A. If the bending radius is not practically usable or has poor impact resistance, or if the bending radius is not practically usable and has poor impact resistance, it is set as B. A comprehensive evaluation is then conducted, and the evaluation result A is set as qualified, while B is set as unqualified.
[0059] [Table 1]
[0060]
[0061] As shown in Table 1, in the electrochemical elements of Examples 1 and 2, the bending radius was practically usable, and the impact resistance was good, resulting in an overall evaluation of A. In the electrochemical element of Comparative Example 1, although the impact resistance was good, the bending radius was not practically usable, resulting in an overall evaluation of B. In the electrochemical element of Comparative Example 2, although the bending radius was practically usable, the impact resistance was poor, resulting in an overall evaluation of B.
[0062] As described above, the embodiments have been illustrated, but these embodiments are provided as examples, and the present invention is not limited to these embodiments. The embodiments described above can be implemented in various other ways, and various combinations, omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their variations are included within the scope and spirit of the invention, and are encompassed within the scope of the claims and their equivalents.
[0063] This international application claims priority based on Japanese Patent Application No. 2024-039702, filed on March 14, 2024, the entire contents of which are incorporated herein by reference.
[0064] Explanation of reference numerals in the attached figures
[0065] 1: Electrochemical Components
[0066] 2: Glass film
[0067] 21: Through hole
[0068] 3: Electrode layer
[0069] 4: Electrolyte layer
[0070] 5: Counter electrode layer
[0071] 10: Electrochemical element roller
Claims
1. An electrochemical element, characterized in that, It sequentially comprises a glass membrane, an electrode layer, and an electrolyte layer that allow gas to pass through, with a bending radius exceeding 20 mm and less than 200 mm. The thickness of the glass film is greater than 20 μm and less than 200 μm.
2. The electrochemical element according to claim 1, characterized in that, The electrolyte layer contains oxides.
3. The electrochemical element according to claim 1 or 2, characterized in that, The glass film has multiple through holes.
4. An electrochemical element roller, characterized in that, It sequentially comprises a long, strip-shaped glass membrane that allows gas to pass through, an electrode layer, and an electrolyte layer, with a bending radius exceeding 20 mm and less than 200 mm. The thickness of the glass film is greater than 20 μm and less than 200 μm.
5. A method for manufacturing an electrochemical element, characterized in that, It has the following steps: While conveying a glass membrane with a thickness of 20μm to 200μm that allows gas to pass through in a roller-to-roll manner, an electrode layer is formed on the glass membrane. An electrolyte layer is formed on the electrode layer; A counter electrode layer is formed on the electrolyte layer.
Citation Information
Patent Citations
Information processing system
JP2024039702A
Metal support type electrochemical element, and method for manufacturing solid oxide type fuel cell and metal support type electrochemical element
WO2017047656A1